Genetic Characterization of Domesticated F1 Generation in Humpback Grouper (Cromileptes altivelis) - Aliah, Ratu Siti; Wahidah, .; Sumantadinata, K.; Nugroho, Estu; Carman, O. (Jurnal Akuakultur Indonesia, 2006)
First generation (F1) of hatchery produced humpback grouper (Cromileptes altivelis) has been characterized genetically in order to serve the information of their status in related to their breeding strategy. PCR-RFLP method was used to detect the variation of mtDNA D-loop region of F1 population at BBPBL Lampung and BBAP Situbondo. The result of study showed that reducing of haplotype diversity had been arised from broodstock (0.8548) to F1 generation population (0.7473; 0.7273; and 0.6947, respectively).  Genetic divergence that had found between population BBPBL Lampung and BBAP Situbondo make it possible to do outbreeding in order to get its heterosis's effect. Keywords: mtDNA, haplotype diversity, genetic differentiation, Cromileptes altivelis   ABSTRAK Ikan kerapu tikus (Cromileptes altivelis) generasi pertama (F1) hasil domestikasi di hatchery telah dikarakterisasi secara genetik untuk menyediakan informasi status sehubungan dengan program pemuliaannya.  Metode PCR-RFLP digunakan untuk mendeteksi variasi sekuens D-loop mtDNA ikan kerapu tikus F1 yang diproduksi di BBPBL Lampung dan BBAP Situbondo.  Hasil penelitian menunjukkan bahwa telah terjadi penurunan keragaman haplotipe dari induk (0,8548) ke populasi generasi F1 (masing-masing 0,7473; 0,7273; dan 0,6947).  Adanya keragaman genetik antara populasi ikan kerapu tikus di BBPBL dan BBAP Situbondo memungkinkan dilakukannya outbreeding untuk mendapatkan efek heterosis. Kata kunci: mtDNA, keragaman haplotipe, diferensiasi genetik, Cromileptes altivelis